Implementasi Load Balancing Di Web Server Menggunakan Metode Berbasis Sumber Daya CPU Pada Software Defined Networking - Riski Julianto; Widhi Yahya; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Nowadays, there has been a great traffic in the network. It is characterized by an increasingly high users will increase the complexity of the network such as increased server load and hard to configure any devices from different vendorss, so there needs to be a good web server. If a single web server, it will cause SPOF (Single Point of Failure). The use of cluster servers with load balancing will improve the performance of web servers implemented in Software Defined Network. Load balancing with resource-based methods is a load-sharing method using the smallest CPU usage of the server as a reference. Through the implementation of the system obtained server divide the load well. Testing with many connections and rate divided into 3 parts that is low to rate 40, medium to rate 80 and high for rate 160. The testing parameters used are throughput, response time, and CPU usage using Httperf and psutil tools. The results of the test obtained with the average throughput value of 947.9 KB / s, response time average of 6.2 ms, and CPU Usage of 59.82% on the first server, 69.73% on the second server and 93,24% on the third server. By comparison of the Round Robin algorithm, the CPU-based method is better than Round Robin based on the tests performed.